Microstructure and Hydrogen Permeability of Nb-Ni-Ti-Zr-Co High Entropy Alloys - Kashkarov, Egor; Krotkevich, Dmitriy; Koptsev, Maxim; Ognev, Sergei; Svyatkin, Leonid; Travitzky, Nahum; Lider, Andrey (Membranes, 2022)
Hydrogen separation membranes are one of the most promising technologies for hydrogen purification. The development of high-entropy alloys (HEAs) for hydrogen separation membranes is driven by a "cocktail effect" of elements with different hydrogen affinities to prevent hydride formation and retain high permeability due to the single-phase BCC structure. In this paper, equimolar and non-equimolar Nb-Ni-Ti-Zr-Co high entropy alloys were fabricated by arc melting. The microstructure and phase composition of the alloys were analyzed by scanning electron microscopy and X-ray diffraction, respectively. The hydrogen permeation experiments were performed at 300-500 degrees C and a hydrogen pressure of 4 bar. In order to estimate the effect of composition and lattice structure on hydrogen location and diffusivity in Nb-Ni-Ti-Zr-Co alloy, ab initio calculations of hydrogen binding energy were performed using virtual crystal approximation. It was found that Nb-enriched and near equimolar BCC phases were formed in Nb20Ni20Ti20Zr20Co20 HEA while Nb-enriched BCC and B2-Ni(Ti, Zr) were formed in Nb40Ni25Ti18Zr12Co5 alloy. Hydrogen permeability tests showed that Nb20Ni20Ti20Zr20Co20 HEA shows lower activation energy and higher permeability at lower temperatures as well as higher resistance to hydrogen embrittlement compared to Nb40Ni25Ti18Zr12Co5 alloy. The effect of composition, microstructure and hydrogen binding energies on permeability of the fabricated alloys was discussed.
CRIS-Team WoS Importer:2022-12-23